Using the Field Trip Method to Improve Student Learning Outcomes in Social Studies Subjects - Putro, Diding Suwarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
"Using the Field Trip Method to Improve Student Learning Outcomes in Social Studies Subjects in Grade V Students at SDN Tegalharjo Surakarta for the 2021/2022 Academic Year". This study aims to determine the increase in student learning outcomes on social studies subjects by using the field trip method. This type of research is classroom action research (PTK).The subjects of this study were the fifth grade students at SDN Tegalharjo Surakarta for the 2021/2022 academic year consisting of 28 children. Based on the results of the study, data from cycle I showed that the average value of the learning outcomes of class V students at SDN Tegalharjo was 68 with the percentage of students' mastery learning being 60%. In cycle II the average value of the learning outcomes of class V students at SDN Tegalharjo increased to 80 with a complete learning achievement percentage of 85%.These results indicate that the field trip method can improve student learning outcomes, especially the social studies class V at SDN Tegalharjo Surakarta.